How tiktok shop drives beauty product purchase intentions among moeslem gen Z women in Medan - Hermawan, Indra (Indonesian Journal of Islamic Economics Research, 2024)
This study investigates the relationship between social commerce constructs, customer trust, and purchase intentions, focusing on the context of beauty products on TikTok. Through a quantitative approach utilizing a survey method, data were collected from moeslem women of Generation Z in Medan City. The research findings indicate a non-significant direct relationship between social commerce constructs and customer trust, suggesting minimal influence of these constructs on trust. Similarly, the direct impact of social commerce constructs on purchase intentions was found to be non-significant. However, a significant positive relationship was observed between customer trust and purchase intentions, highlighting the pivotal role of trust in driving purchase decisions. The study emphasizes the importance of fostering customer trust to enhance purchase likelihood in social commerce environments. While direct effects of social commerce constructs on trust and purchase intentions may be limited, efforts to build and maintain customer trust are crucial for boosting purchase intentions effectively. Further research and model refinement are recommended to explore additional factors influencing these dynamics.